Sovereign Wealth Funds: An Exploratory Study of Their Behavior - Ali Fatemi; Iraj Fooladi; Nargess Kayhani (The Journal of Entrepreneurial Finance (JEF), 2011)
Sovereign wealth funds have recently moved to the front and center of discussion, both within the investment world and the political arena. In this paper we evaluate the differences and common features of these funds. Utilizing an ownership database, we probe the ownership, geographic, and industry concentration of the funds deployed by these entities. We also compare and contrast the main features of two of the largest sovereign wealth funds.
Keywords: F02; F36; G15; 650; Sovereign Wealth Fund